Population Evolution of Helicobacter pylori through Diversification in DNA Methylation and Interstrain Sequence Homogenization. (7th September 2016) - Kojima, Kenji K.; Furuta, Yoshikazu; Yahara, Koji; Fukuyo, Masaki; Shiwa, Yuh; Nishiumi, Shin; Yoshida, Masaru; Azuma, Takeshi; Yoshikawa, Hirofumi; Kobayashi, Ichizo
Abstract: Decoding of closely related genomes is now revealing the process of population evolution. In bacteria, population divergence appears associated with a unique set of sequence-specific epigenetic DNA methylation systems, often within restriction–modification (RM) systems. They might define a unique gene expression pattern and limit genetic flux between lineages in population divergence. We addressed the contribution of methylation systems to population diversification in panmictic bacterial species, Helicobacter pylori, which shows an interconnected population structure through frequent mutual recombination. We analyzed complete genome sequences of 28 strains collected in Fukui, Japan. Their nucleotide sequences are closely related although fine-scale analyses revealed two subgroups likely reflecting human subpopulations. Their sequences are tightly connected by homologous recombination. Our extensive analysis of RM systems revealed an extreme variability in DNA methyltransferases, especially in their target recognition domains. Their diversity was, however, not immediately related to the genome sequence diversity, except for very closely related strains. An interesting exception is a hybrid strain, which likely has conserved the methylation gene repertoire from one parent but diversified in sequence by massive acquisition of fragmentary DNA sequences from the other parent. Our results demonstrate how a bacterial population can be extremely divergent in epigenetics and yet homogenized in sequence.